Physicochemical, functional and rheological characterization of passion fruit shell flour (Passiflora edulis SIMS) - Chuqui-Diestra, Saúl Ricardo (2021)
Passion fruit peel is an agro-industrial waste that with added value can be used in the food industry. The purpose of this work was the physicochemical, functional and rheological characterization of passion fruit shell flour (HCMr). Physicochemical, functional and rheological analyzes were carried out. The humidity value of HCMr was 11.25%, this is within the requirements of Peruvian standards. Protein values (5.14%) are low compared to cerelae flours. The total dietary fiber value was 63.88%. The total values of polyphenols and antioxidant activity were 504.75 mg G.A.E./100g and 1520.49 µmol ET / 100g respectively. The water retention capacity value was 12.93 ml retained water / g. The rheological values were: 702 consistency farinographic units with 14.02% humidity. With these characteristics obtained, HCMr can be used as an ingredient or food substitute and thus obtain products with important nutritional benefits.